2018
DOI: 10.3389/fncel.2018.00258
|View full text |Cite
|
Sign up to set email alerts
|

Importance of GPCR-Mediated Microglial Activation in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder associated with impairment of cognition, memory deficits and behavioral abnormalities. Accumulation of amyloid beta (Aβ) is a characteristic hallmark of AD. Microglia express several GPCRs, which, upon activation by modulators, mediate microglial activation and polarization phenotype. This GPCR-mediated microglial activation has both protective and detrimental effects. Microglial GPCRs are involved in amyloid precursor protein (APP) cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 254 publications
(283 reference statements)
1
27
0
Order By: Relevance
“…Currently, analysis of the pathophysiology of neurodegeneration represents a great challenge for scientist [[175], [176], [177]]. Copious scientific articles have reported neuroprotective activity of natural constituents on the various model of neurodegeneration.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Currently, analysis of the pathophysiology of neurodegeneration represents a great challenge for scientist [[175], [176], [177]]. Copious scientific articles have reported neuroprotective activity of natural constituents on the various model of neurodegeneration.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Although very little is known about their endogenous or exogenous ligands, these so-called oGPCRS have gained considerable attention as drug targets [163]. Several findings have postulated the critical role of oGPCRs in the cognitive deficits in disorders such as AD and schizophrenia [164][165][166][167]. For example, an expression map of the mouse brain has listed 78 oGPCRs and showed that many of them are relevant to cognition, motivation, and emotional processing [168].…”
Section: Orphan Gpcrsmentioning
confidence: 99%
“…The neurotoxic phenotype express iNOS and major histocompatibility complex (MHC) II, activating the NF-κB pathway to produce several pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-6, IL-12 and IL-23, and generate ROS and NO, which subsequently induce immune stimulation, neuroinflammation, the block of axonal remodeling and prevent neurogenesis. However, neuro-protective phenotypes mediate neuroprotection by Aβ phagocytosis and clearance, neuronal regeneration modulation, and arginase 1 (Arg1) release for tissue remodeling, wound healing and debris clearance [80].…”
Section: Microglia Modulation and Neuro-inflammation Inhibitionmentioning
confidence: 99%